Ideological Dimensions in the Translation of Hillary Clinton’s Memoir Hard Choices - Mehawesh, Mohammad Issa (Forum for Linguistic Studies, 2025)
This research examines the ideological dimensions present in the Arabic translation of Hillary Clinton’s memoir Hard Choices. The study explores how translation strategies—particularly literal translation, modulation, adaptation, and omission—are employed not only to convey linguistic meaning but also to shape and mediate critical ideological themes. Among these are the promotion of democracy, constructions of national identity, gender roles, and diplomatic rhetoric. The analysis demonstrates that translation is far from a neutral or mechanical transfer of information. Rather, it is a complex, multilayered process in which political, cultural, and ideological values are reframed to suit the expectations and sensitivities of the target audience. The findings suggest that the translator plays an active and engaged role in ideological negotiation, either by preserving the ideological stance of the source text or by modifying it to align with the cultural and political norms of the target language context. Through detailed examination of selected examples, the research reveals how certain ideological messages are reinforced, diluted, or subtly transformed through specific lexical and syntactic choices. These choices reflect broader considerations, such as audience alignment, political sensitivity, and cultural acceptance. Thus, translation emerges not only as an act of cross-linguistic communication but also as a site of ideological struggle and intervention. Overall, the study highlights the significant role of the translator as a mediator of meaning and ideology, showing that translated political texts can influence the reception and interpretation of global political narratives across different linguistic and cultural spheres.